Central venous catheter related blood stream infection in tertiary care hospital - Sawant, Ankita R.; Paritekar, Anita A. (International Journal of Research in Medical Sciences, 2024)
Background: Central venous catheter-related bloodstream infections (CRBSIs) are associated with significant morbidity and mortality in hospitalized patients. Understanding the incidence and risk factors associated with CRBSIs is crucial for implementing effective preventive strategies. The study aimed to examine the incidence and risk factors associated with central venous CRBSIs in a tertiary care hospital setting. Methods: A prospective observational study was conducted at a tertiary care hospital to investigate the incidence and risk factors of CRBSIs. Patients aged >18 years with a central venous catheter inserted for >48 hours were included. Clinical and microbiological data were collected, and CRBSI rates were calculated. Statistical analysis was performed using SPSS V 23.0. Results: A total of 50 patients were recruited, with 11 diagnosed with CRBSIs. The incidence of CRBSIs was 8.1 per 1000 central line days and 5.7 per 1000 inpatient days, with a Device Utilization Ratio (DUR) of 0.7. Male gender and older age (>40 years) were significantly associated with CRBSIs (p<0.05). Gram-negative microorganisms were the most commonly isolated pathogens (63.63%), followed by Gram-positive organisms (27.27%) and Candida species (9.09%). Immune system status (p=0.0372) and duration of catheterization (P=0.0035) were found to have a significant association with CRBSI. Mortality was higher in patients with CRBSIs compared to those without (45.45% vs. 28.21%). Conclusions: CRBSIs remain a significant concern in tertiary care hospitals, with Gram-negative organisms being the predominant pathogens. Male gender and older age were identified as risk factors for CRBSIs. Effective infection control measures targeting high-risk populations are warranted to reduce the incidence of CRBSIs and improve patient outcomes.